Biometanização de diferentes frações de resíduos alimentares em temperaturas mesofílica e termofílica - Rodrigues, Vitor [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
In Brazil, about 50% of the total solid urban waste is organic waste, less than 3% of this percentage has some type of reuse. Anaerobic digestion presents itself as an efficient alternative, since it reuses the organic waste for the generation of biofertilizers and biogas and reduces the volume of waste destined to sanitary landfills. In this way, this work evaluated the biomethanization process of different fractions of food waste generated in the university restaurant of UNESP - Rio Claro Campus (SP), in mesophilic and thermophilic temperatures. Two categories were created for the food waste: pre-preparation (vegetables) and leftovers (rice and beans). Biochemical potential of methane generation (BMP) tests were carried out, using as inoculum source two types of sludge from UASB reactors: vinasse treatment and treatment of effluent from a poultry slaughterhouse. Accumulated methane production and analysis of COD, BOD, Total Carbohydrate, pH and STV, were used to evaluate the efficiency of the process. In the tests with different temperatures, the substrate / inoculum ratio used was 1:1. The results obtained in the thermophilic test indicated higher values of BMP (0.671, 0.640 m3 CH4 kg STVadic -1) for most fractions of waste. From the fraction of food waste that presented one of the highest accumulated methane yields (75% pre-preparation residues and 25% leftover residues) and which was compatible with the generation of food waste from the restaurant, different substrate / inoculum ratios (0.5, 1.0, 1, 5, 2.0 and 3.0) were used to evaluate the maximum rate of organic loading. The results indicated that the best substrate / inoculum ratios were 0.5 and 1.0, with BMP values of 0.671 and 0.641 m3 CH4 kg STVadic -1, respectively. In addition, the best values found in the carbohydrate consumption, COD removal and BOD removal tests were 99.7%, 82.66% and 86.89%, respectively. Thus, through the results obtained it is concluded that it is possible to...

No Brasil, cerca de 50% do total de resíduos sólidos urbanos é representado por resíduos orgânicos, sendo que menos de 3% desse percentual possui algum tipo de reaproveitamento. A digestão anaeróbia se apresenta como uma alternativa eficiente, uma vez que reaproveita os resíduos orgânicos para a geração de biofertilizantes e biogás e diminui o volume de resíduos direcionados a aterros sanitários. Dessa forma, esse trabalho avaliou o processo de biometanização de diferentes frações de resíduos alimentares gerados no restaurante universitário da UNESP - Campus de Rio Claro (SP), em temperaturas mesofílica e termofílica. Os resíduos alimentares foram divididos em duas categorias: pré-preparo (cascas de legumes e vegetais) e sobras (arroz e feijão). Foram realizados testes de potencial bioquímico de geração de metano (BMP), tendo como fonte de inóculo dois tipos de lodo provenientes de reatores UASB: tratamento de vinhaça e tratamento de efluente de um abatedouro de aves. A eficiência do processo foi avaliada através da produção acumulada de metano e de análises de DQO, DBO, Carboidratos Totais, pH e STV. Nos testes com diferentes temperaturas foi empregada a relação substrato/inóculo de 1:1. Os resultados obtidos no teste termofílico indicaram maiores valores de BMP (0,671; 0,640 m3 CH4 kg STVadic. -1) para a maioria das frações de resíduos. A partir da fração de resíduos que apresentou uma das maiores produções acumulada de metano (75% de resíduos de pré-preparo e 25% resíduos de sobras) e que era compatível com a geração de resíduos alimentares do restaurante, foram testadas diferentes relações substrato/inóculo (0,5, 1,0, 1,5, 2,0 e 3,0) para avaliar a taxa máxima de carregamento orgânico. Os resultados indicaram que as melhores relações substrato/inóculo foram 0,5 e 1,0, com valores de BMP de 0,671 e 0,641 m3 CH4 kg STVadic. -1, respectivamente. Além disso, os melhores valores...
Keywords: Universidade Estadual Paulista Júlio de Mesquita Filho Instituto de Biociências (Campus de Rio Claro); Universidade Estadual Paulista Júlio de Mesquita Filho Instituto de Geociências e Ciências Exatas; Resíduos; Metano; Biogas; Resíduos sólidos; Residuos organicos - Reaproveitamento; Digestão anaeróbia; Biofertilizantes; Energia - Fontes alternativas; Rio Claro (SP); Brasil